1993
DOI: 10.1111/j.1745-6606.1993.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Generalizability of a Scale for Profiling Consumers' Decision‐Making Styles

Abstract: Most studies that have developed and validated models and instruments in consumer affairs research have used U.S. samples. As a result, their cross-cultural generalizability remains unknown. This study reports a cross-cultural examination of a scale for profiling consumers' decision-making styles using a New Zealand sample. Examination of the scale's psychometric properties (i.e., dimensionality and reliability) offers general support for the scale's applicability to a different culture. Some differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
144
1
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(151 citation statements)
references
References 16 publications
2
144
1
4
Order By: Relevance
“…Indeed, Sproles and Kendall 22 requested that 'to establish generality further, [the CSI] must be administered to other populations'. Several authors have responded and replications have been carried out in South Korea, 23 New Zealand, 24 Greece, the USA, India and New Zealand, 25 Great Britain 26 and China. 27,28 The original structure of decision-making style, by and large, was confirmed in all seven countries.…”
mentioning
confidence: 99%
“…Indeed, Sproles and Kendall 22 requested that 'to establish generality further, [the CSI] must be administered to other populations'. Several authors have responded and replications have been carried out in South Korea, 23 New Zealand, 24 Greece, the USA, India and New Zealand, 25 Great Britain 26 and China. 27,28 The original structure of decision-making style, by and large, was confirmed in all seven countries.…”
mentioning
confidence: 99%
“…However, they formed two different factors in our study and it can be said that this may have resulted from cultural differences. This can be seen from other studies in which different consumer styles have been obtained in various countries and cultures (Hafstrom, et al, 1992;Durvasula et al, 1993;Lysonski, et al, 1996;Fan and Xiao, 1998;Hiu et al, 2001;Walsh et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…In these studies, some characteristics have been found to be similar while others have been found to be different in various countries (Hafstrom et al, 1992;Durvasula et al, 1993;Lysonski et al, 1996;Fan andXiao, 1998, Hiu et al, 2001;Walsh et al, 2001;Tai, 2005). In a study carried out by Bauer, Sauer and Beeker in 2002, consumer styles with respect to convenience goods and shopping goods were examined.…”
Section: Consumer's Decision-making Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers (Durvasula, Lysonski & Andrews, 1993;Visser & Du Preez, 1998;Visser, Du Preez & Du Toit, 1996) have emphasised that data and models that were developed in the United States cannot be accepted as valid in other countries. This issue is addressed in the present research project by using universal consumer behaviour models and applying them to a South African context.…”
Section: Motivation For Building Theoretical Modelsmentioning
confidence: 99%